2021
DOI: 10.1002/qj.4185
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of convective precipitation over tropical Africa in storm‐resolving global simulations

Abstract: We analyse how the representation of deep convection affects the characteristics of convective precipitation over tropical Africa in global storm-resolving simulations with the European Centre for Medium-Range Weather Forecasts (ECMWF) Integrated Forecasting System (IFS). The simulations consist in 48 hr forecasts initiated daily at 0000 UTC for a 40-day period in August and September 2016, at ∼9 and 4 km resolution. We find that results agree best with the satellite retrieval Global Precipitation Measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 81 publications
(107 reference statements)
8
35
0
Order By: Relevance
“…While over 90% of the tropical rainfall was explicitly resolved, the convective parameterization still contributed a small fraction of rainfall in that region. It is possible, although unproven, that the scale‐aware convective parameterization mitigated some issues of global models with entirely resolved deep convection, such as the production of overly intense rainfall extremes or the lack of organized convective systems (e.g., Becker et al., 2021). This issue must be investigated to explore the possibility of using scale‐aware convection parameterizations even when global models move to grid spacings smaller than 10 km (Freitas et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While over 90% of the tropical rainfall was explicitly resolved, the convective parameterization still contributed a small fraction of rainfall in that region. It is possible, although unproven, that the scale‐aware convective parameterization mitigated some issues of global models with entirely resolved deep convection, such as the production of overly intense rainfall extremes or the lack of organized convective systems (e.g., Becker et al., 2021). This issue must be investigated to explore the possibility of using scale‐aware convection parameterizations even when global models move to grid spacings smaller than 10 km (Freitas et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Judt and Rios‐Berrios (2021) further showed that the improved representation of rainfall variability stemmed from explicitly resolving convection because their simulations with sub 10 km cell spacing and a convection parameterization did not show improvements over the simulations with 15 km cell spacing or greater. Not all aspects of tropical rainfall are improved in global models with explicit convection; for instance, resolving convection can produce overly intense rainfall that precludes the formation of mesoscale convective systems (Becker et al., 2021; Stevens et al., 2019).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The moist physics upgrade also addresses errors in the parametrization of deep convection, especially for the representation of propagating mesoscale convective systems and their diurnal cycle. In particular, insufficient night-time convection over land has been identified as a major shortcoming in IFS forecasts of convective activity (Becker et al, 2021;Forbes et al, 2021).…”
Section: New Moist Physicsmentioning
confidence: 99%
“…One approach to improving the representation of convective organization in these schemes could be an explicit inclusion of large‐scale circulations in their closure formulation. One recent study has shown that coupling a convection scheme to the mesoscale dynamics (by including an advective moisture tendency term to the mass flux closure) improved both the organization and propagation of deep convective systems (Becker et al., 2021). Note, however, this approach would only impact the behavior of a 3D but not 1D setup, given that the additional moisture convergence term would not result in any changes in an SCM configuration.…”
Section: Discussionmentioning
confidence: 99%